A Cross-Sectional Survey on Burnout Prevalence and Profile in the Sicilian Population of Ambulance Driver-Rescuers. Issue 2 (27th January 2020) - Ferraro, Laura; La Cascia, Caterina; De Santis, Antonio; Sideli, Lucia; Maniaci, Giuseppe; Orlando, Ilenia Maria; Chifari, Angelo; Maniaci, Lorenzo; La Barbera, Daniele
Abstract: Introduction: Burnout is present at a high rate in emergency medicine. The ambulance driver-rescuers, who furnish first aid to the victims, are the non-medical part of the Italian 118-service staff. There is a lack of research on burnout risk in Italian Emergency Medical Services and, particularly, for this category of workers. The two Italian studies, including a little group of ambulance driver-rescuers, reported inconsistent findings. Hypothesis: This survey investigated for the first time the prevalence and exact profile of burnout in a large sample of Italian driver-rescuers. As a secondary aim, the study described how the items of the Italian version of the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) cluster in components in this sample. Methods: This cross-sectional census survey was conducted from June 2015 through May 2016 and involved all the driver-rescuers operating in Sicily, the biggest and most southern region of Italy. The subjects received a classification according to different profiles of burnout by using the Italian version of the MBI-HSS (burnout, engagement, disengagement, over-extension, and work-inefficacy). In order to explore the existence of independent factors, a Principal Component Analysis (PCA) was conducted on the survey to obtain eigenvalues >one for each component in the data. Results: The final sample comprised 2, 361 responders (96.6% of the initial sample). Of them, 29.8% were in burnout (95% confidence interval [CI], 27.8% to 31.8%) and 1.7% presented a severe form (95% CI, 1.1% to 2.3%); 30.0% were engaged in their work (95% CI, 21.0% to 34.8%), 24.7% of responders were disengaged (95% CI, 22.9% to 26.5%), 1.2% presented an over-extension profile (95% CI, 0.8% to 1.7%), and 12.6% felt work-inefficacy (95% CI, 11.3% to 14.1%). The factors loaded into a five-factor solution at PCA, explaining 48.1% of the variance and partially replicating the three-factor structure. The Emotional Exhaustion (EE) component was confirmed. New dimensions from Personal Accomplishment (PA) and Depersonalization (DP) sub-scales described empathy and disengagement with patients, respectively, and were responsible for the increased risk of burnout. Conclusions: These results endorse the importance of screening and psychological interventions for this population of emergency workers, where burnout could manifest itself more insidiously. It is also possible to speculate that sub-optimal empathy skills could be related to the disengagement and work-inefficacy feelings registered.